Original papersIsovolumic contraction acceleration before and after percutaneous closure of atrial septal defects - Tosu, Aydın Rodi; Gürsu, Özgür; Aşker, Müntecep; Etli, Mustafa; İşcan, Şahin; Eker, Esra; Köksal, Ceren; Polat, Vural (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Aim: To compare systemic right ventricular function by isovolumic myocardial acceleration before and 6 months after the percutaneous closure of atrial septal defects (ASD). Material and methods : Patients admitted to our tertiary center for the percutaneous closure of atrial septal defects between January 2010 and August 2012 constituted the study group. Right ventricular function of patients was assessed by tissue Doppler echocardiography before and after surgery. Echocardiographic data in patients were compared to age-matched controls without any cardiac pathology and studied in identical fashion mentioned below. Results : A total of 44 patients (24 males, 20 females) and 44 age-matched controls (25 males, 19 females) met the eligibility criteria for the study. Right ventricular end-diastolic and end-systolic volume, right ventricular end-diastolic diameter measurements on echocardiogram, and pulmonary artery pressures in both pre- and post-ASD groups were significantly higher than in controls. Tricuspid annular plane systolic excursion and isovolumic myocardial acceleration measurements significantly increased after the percutaneous closure of the defect; however, post-ASD measurements were still significantly lower than the controls. Conclusions : Atrial septal defect device closure resulted in a significant increase of isovolumic myocardial acceleration measurements. Tissue Doppler analysis of regional myocardial function offers new insight into myocardial compensatory mechanisms for acute and chronic volume overload of both ventricles.